PENGARUH MODAL KERJA TERHADAP TINGKAT PROFITABILITAS PADA PT. ADIRA DINAMIKA MULTI FINANCE TBK. - Chaerunnisa Rumianti (Contemporary Journal on Business and Accounting, 2021)
Purpose – This study to test and analyze influence the effect of working capital on the level of profitability at PT. Adira Dinamika Multi Finance Tbk Design/methodology/approach – The data analysis technique used in this research is descriptive statistical analysis, classical assumption test, paired samples t-test, simple linear regression test, t test and hypothesis test. Findings – Working capital (DER) which has a negative effect is proven to decrease the profitability (ROA) of PT. Adira Dinamika Multi Finance, Tbk Originality – The population is the report on 2009-2019 accounting for 11 years at PT. Adira Dinamika Multi Finance Tbk Keywords: Working Capital, Profitability Paper Type Research Result